The role of IGF-2 and its variants in enhancing endothelial migration and angiogenesis - Alders, Lotte; Pirlet, Elke; Gesquiere, Emma; Bronckaers, Annelies (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAngiogenesis, the formation of new blood vessels, is essential for physiological processes such as tissue repair as well as pathological conditions including cancer. While insulin-like growth factor 2 (IGF-2) is identified as a key regulator of angiogenesis, the contributions of its variants remain less explored.MethodsWe compared the effects of wildtype IGF-2 with that of Des(1-6)IGF-2, which has lower affinity to IGF-binding proteins (IGFBPs), and Leu27IGF2, which interacts selectively with the IGF-Receptor 2. We analyzed their effect on endothelial cell migration and tube formation as well as on the secretome of endothelial cells using an antibody array. In addition, the regulatory influence of IGF-binding protein 6 (IGFBP-6) in modulating these effects was investigated. Finally, the ability of the three different variants of IGF-2 to induce blood vessel formation was studied using the chicken ‘chorioallantoic membrane’ (CAM) assay.ResultsIGF-2 and Des(1-6)IGF-2 significantly promoted endothelial cell migration and tube formation in vitro, while also increasing blood vessel formation in ovo. An angiogenesis antibody array revealed that these effects were mediated through the upregulation of several angiogenic proteins, including IL-6, uPAR, and MCP-1. Interestingly, Leu27IGF-2 exhibited a weaker effect, suggesting that IGF receptor 1 and/or insulin receptor activation plays a major role in these processes. IGFBP-6 effectively inhibits IGF-2-induced effects but has no impact on Des(1-6)IGF-2, highlighting the latter’s ability to evade IGFBP-mediated inhibition due to structural modifications.ConclusionThese results suggest that Des(1-6)IGF-2 may serve as a potent pro-angiogenic agent with therapeutic potential, while IGFBP-6 could offer a strategy for suppressing pathological angiogenesis.